Potensi Pengembangan Tumpang Sari Kedelai di Perkebunan Kelapa Sawit Belum Menghasilkan di Provinsi Riau - Nurhayati Nurhayati; Usman Usman; Emisari Ritonga; Ida Nur Istina (xxxx-xxxx, 2020)
Nurhayati N, Usman U, Ritonga E, Istina IN.  2020.  Development Potential soybeans intercropping in immature palm oil at Riau province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Indonesian soybean production has only fulfilled 56% of national needs. Soybean production can still be increased through the application of technological innovations to increase productivity and utilization of immature oil palm plantations. The area of oil palm plantations in Riau continues to expand from 2.01 million ha in 2016 to 2.7 million ha and 2018. Soybean development in oil palm plantations can be done, on immature plants, mature plants and damaged crops land with a potential area of 821,067 ha. Efforts to develop soybeans in oil palm plantation areas with shade-tolerant soybean VUB technology, improvement of soil fertility through amelioration, organic fertilizers and N, P and K. fertilizers can contribute to the fulfilment of soybean needs at least 17.10% of the national requirement.